2022
DOI: 10.1186/s12951-022-01342-8
|View full text |Cite
|
Sign up to set email alerts
|

The advances in nanomedicine for bone and cartilage repair

Abstract: With the gradual demographic shift toward an aging and obese society, an increasing number of patients are suffering from bone and cartilage injuries. However, conventional therapies are hindered by the defects of materials, failing to adequately stimulate the necessary cellular response to promote sufficient cartilage regeneration, bone remodeling and osseointegration. In recent years, the rapid development of nanomedicine has initiated a revolution in orthopedics, especially in tissue engineering and regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 343 publications
(349 reference statements)
0
39
0
Order By: Relevance
“…In previous studies, metal and its oxides have shown many unique physical and chemical properties, such as the surface plasmon resonance of gold nanoparticles and the broad-spectrum antibacterial properties of silver nanoparticles, and these characteristics can bring more great properties to nanocomposite hydrogels and expand their scope of application ( Qiao et al, 2022 ). For instance, silver nanoparticles (Ag-NPs) have superior antibacterial properties and are widely used in anti-infection and implant surface coating ( Barani et al, 2012 ).…”
Section: Nanoparticles Applied In Cartilage Regenerationmentioning
confidence: 99%
“…In previous studies, metal and its oxides have shown many unique physical and chemical properties, such as the surface plasmon resonance of gold nanoparticles and the broad-spectrum antibacterial properties of silver nanoparticles, and these characteristics can bring more great properties to nanocomposite hydrogels and expand their scope of application ( Qiao et al, 2022 ). For instance, silver nanoparticles (Ag-NPs) have superior antibacterial properties and are widely used in anti-infection and implant surface coating ( Barani et al, 2012 ).…”
Section: Nanoparticles Applied In Cartilage Regenerationmentioning
confidence: 99%
“…The obtained nanocomposite supports osteoblast cell growth and osteoblast adhesion along with good mechanical properties. 189 However, without the presence of different nanostructures (organic, inorganic, and polymeric) near the PSA matrix, improving the mechanical features [190][191][192] was completely impossible.…”
Section: Advanced Applications Of Polysaccharides In Biomedical Engin...mentioning
confidence: 99%
“…Therefore, strict requirements about the release kinetics of therapeutic molecules are necessary for treating bone infection, inflammation or defect. A few emerging technologies, including tissue engineering material transplantation ( Liu J. Y. et al, 2021 ), stem cell technology ( Shang et al, 2021 ), and nanomedicine ( Qiao K. et al, 2022 ), are potential means to promote the treatment of complex bone diseases. In particular, nanomedicine, based on various nanobiomaterials has significantly accelerated the diagnosis research, treatment, and regeneration of bone diseases, and has obtained numerous achievements ( Chen et al, 2020 ; Hagaman et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%